The Immortal Count : The Life and Films of Bela Lugosi - Lennig, Arthur (Book collections on Project MUSE., 2003)
In the 1931 film Dracula, Bela Lugosi set the standard for horror film villainy. Though many actors have donned the cape since that first production, remnants of Hungarian-born Lugosi's portrayal continue to surface in popular culture -- from highly prized memorabilia to a character on Sesame Street. After a decade of trying vainly to broaden his range, Lugosi gave up his ambitions and began to support himself with roles that were all in some way a variation of the first. Ultimately, Lugosi became a sad parody of his former self, and the last years of his life were marked by financial crise.